Simulation of laminar natural convection in a porous cylindrical annulus with double-diffusion effects - Tofaneli, Luzia Aparecida (2010)
This paper presents results for coupled heat and mass transport under laminar flow regime in a horizontal cylindrical annulus filled with a fluid saturated porous medium. Two driving mechanisms are considered to contribute to the overall momentum transport, namely temperature driven and concentration driven mass fluxes. Aiding and opposing flows are considered, where temperature and concentration gradients are either in the same direction or of different sign, respectively. Modeled equations are presented based on the double-decomposition concept, which considers both time fluctuations and spatial deviations about mean values.